Didactic innovation in teachers training - Umpiérrez Oroño, Silvia (2021)
The work values an innovation with ICT in pre professional practice in teacher training. Six quasi experimental instances were organized in which didactic trainers wi th students carried out analysis and reflection on 360 ° film units. Three non participant observations were carried out on these instances, surveys (n = 39), seven semi structured interviews and a documentary study of six productions by the participants ( teachers and students). They valued the devices (film units) for constituting a low risk learning environment, fostering collaboration among students, and adapting to their available times. The devices generated constitute a learning tool that acquires val ue more for the didactic intervention that is carried out with them, than for t heir technical characteristics.